2017
DOI: 10.1007/s00277-017-3147-y
|View full text |Cite
|
Sign up to set email alerts
|

SMABcare study: subcutaneous monoclonal antibody in cancer care: cost-consequence analysis of subcutaneous rituximab in patients with follicular lymphoma

Abstract: Rituximab is used as a standard of care for follicular lymphoma and is usually administered intravenously. A novel subcutaneous formulation recently showed non-inferior efficacy with similar pharmacokinetic and safety profiles compared to intravenous rituximab in patients with follicular lymphoma. This new approach is promising in terms of comfort for patients and time-saving for hospital staff. To evaluate the real-life economic impact of subcutaneous rituximab as maintenance therapy in patients with follicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Their rating of health state in the visual analogue scale was good, with an average score of approximately 75 on a scale where 0 is the worst imaginable health state and 100 is the best imaginable state, and the index preference values (tariffs) also denoted good health, with average values of 0·8–0·9 on a scale where 0 is death and 1 is the best health state. The use of another version of the EQ‐5D during the administration of subcutaneous rituximab maintenance monotherapy to FL patients also reported an overall perception of their health state and quality of life (Fargier et al , ). Hence, most patients expressed no problems in mobility, self‐care or performing their usual activities.…”
Section: Discussionmentioning
confidence: 99%
“…Their rating of health state in the visual analogue scale was good, with an average score of approximately 75 on a scale where 0 is the worst imaginable health state and 100 is the best imaginable state, and the index preference values (tariffs) also denoted good health, with average values of 0·8–0·9 on a scale where 0 is death and 1 is the best health state. The use of another version of the EQ‐5D during the administration of subcutaneous rituximab maintenance monotherapy to FL patients also reported an overall perception of their health state and quality of life (Fargier et al , ). Hence, most patients expressed no problems in mobility, self‐care or performing their usual activities.…”
Section: Discussionmentioning
confidence: 99%
“…All the previously published studies show a better pharmacoeconomic profile of the SC presentations of rituximab and other multiple drugs,24,6,9,10 and the results are repeated in different countries and health systems 9,11,12–20. No known previous work showed higher costs related to SC presentations when compared to IV, so the results are very consistent, and the data have been extensively validated.…”
Section: Discussionmentioning
confidence: 55%
“…Also, the evaluation of the nursing team was not taken into account where more than 94% prefer the SC route,3,25 or from the caregivers with 68% reported to prefer the SC presentation,3 and neither has the impact on the quality of life been analyzed in this study. One study showed that even though a better experience for the patient was reported, the quality of life was not modified 11…”
Section: Discussionmentioning
confidence: 99%
“…16 EQ VAS scores were reported in 28 (44%) of the articles. [16][17][18][19]22,25,28,29,31,34,36,37,39,41,44,46,47,49,58,66,67,69,71,[72][73][74][75][76] We do not present detailed descriptive system results or VAS scores here as this will be the subject of a separate publication.…”
Section: Eq-5d Findingsmentioning
confidence: 99%